Barsaat ki pehli barish - Kashifa, Samad (book group Karachi, 2014)
"Khushboo" is a popular Urdu textbook series used in Pakistani schools, particularly for primary classes. It's designed to introduce young learners to the basics of Urdu language, including reading, writing, and comprehension.